Reconstruction of Political Ideology Through Ad Hominem Argument Strategy in the 2024 Presidential-Vice Presidential Debate - Firdaus, Saiyidinal; Kamal, Muhammad; Anoegrajekti, Novi (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This research critically investigates the reconstruction of political ideology through the use of ad hominem argument strategies in the 2024 Indonesian presidential and vice-presidential debates. Integrating van Dijk’s Critical Discourse Analysis (CDA) and Korta & Perry’s Critical Pragmatics, the study examines five official debate transcripts to identify various forms of ad hominem arguments, their usage patterns, and their persuasive impact on public perceptions. The findings reveal that explicit and implicit ad hominem strategies are systematically deployed by candidates to attack the personal character, credibility, and group affiliation of rivals, while simultaneously reinforcing their own image as agents of change, justice, or moral leadership. These rhetorical moves construct clear moral dichotomies—delineating “us” versus “them”—and intensify political polarization and identity-based mobilization. Furthermore, ad hominem arguments often overshadow substantive policy discussions, shifting the focus of public debate towards personal character and away from programmatic vision. The persuasive impact of these strategies is evident in heightened group loyalty, emotional engagement, and a reduction in the deliberative quality of democratic discourse. The novelty of this study lies in its integrative methodological approach and its focus on the Indonesian context, where political debates are highly influenced by identity politics and polarization. The research not only advances theoretical understanding of rhetorical and ideological dynamics in contemporary political communication but also offers practical recommendations for strengthening political literacy, ethical debate moderation, and responsible media reporting. Ultimately, the findings underscore the urgent need for critical literacy to counteract the divisive effects of ad hominem in democratic discourse.